Latar Belakang Dan Pemikiran Ahli Majlis Penasihat Syariah (Mps) Di Malaysia Dan Implikasinya Terhadap Pembinaan Produk Pembiayaan Perumahan - Ismail, Suraya (2014)
The need to establish the Shariah Advisory Committee (MPS) in the Islamic banking institutions (IPI) as well as the monitoring by the Bank Negara Malaysia MPS at the national level has made the IPI Shariah governance framework more comprehensive. Nevertheless, the debate on the decisions and practices of Islamic banking products are still ongoing. The question is, why do these disputes arise when the verification and approval on the products are made by competent bodies? Based on the application of two different Shariah concepts in the home financing product that is bai` bithaman ajil (BBA) and musharakah mutanaqisah (MM), this study attempts to examine the implications of the background and thoughts of the members of the MPS on the practice of developing Islamic banking products. The review of the overall background of all MPS members in locally owned IPI were carried out using secondary data obtained from documents while aspects of their thoughts were examined through an empirical study. All data were analyzed using content analysis. The study found that the background of the MPS members were dominant in the field of religious studies followed by areas of Islamic law (Shariah) and the field of Islamic transactions (muamalat). In terms of experience, only 11.1 per cent of the members have served in MPS for a period 10 years and more and most of them are from the education sector. An analysis of the application of the Shariah concept in home financing shows the MM concept is more acceptable than the BBA concept.